2019
DOI: 10.1186/s12873-019-0297-3
|View full text |Cite
|
Sign up to set email alerts
|

What are emergency ambulance services doing to meet the needs of people who call frequently? A national survey of current practice in the United Kingdom

Abstract: BackgroundEmergency ambulance services are integral to providing a service for those with unplanned urgent and life-threatening health conditions. However, high use of the service by a small minority of patients is a concern. Our objectives were to describe: service-wide and local policies or pathways for people classified as Frequent Caller; call volume; and results of any audit or evaluation.MethodWe conducted a national survey of current practice in ambulance services in relation to the management of people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…Frequent users of emergency medical systems can sometimes be difficult to identify (Maruster et al, 2020), and interventions have demonstrated promise, but still lack robust data on effectiveness requiring further evaluation (see e.g. Agarwal et al, (2019) and Snooks et al, (2019)). Social prescribing therefore has the potential to be an alternative or supplementary approach to support patients within the pre-hospital emergency and urgent care setting and to reduce the burden on emergency departments and primary care.…”
Section: Macromentioning
confidence: 99%
“…Frequent users of emergency medical systems can sometimes be difficult to identify (Maruster et al, 2020), and interventions have demonstrated promise, but still lack robust data on effectiveness requiring further evaluation (see e.g. Agarwal et al, (2019) and Snooks et al, (2019)). Social prescribing therefore has the potential to be an alternative or supplementary approach to support patients within the pre-hospital emergency and urgent care setting and to reduce the burden on emergency departments and primary care.…”
Section: Macromentioning
confidence: 99%
“…[2][3][4] Studies of frequent EMS use have focused largely on adult populations, where a combination of physical health, mental health and social problems including isolation and loneliness contribute to frequent use. [5 6] There are now efforts to proactively identify and manage adult frequent EMS users to better meet their needs, [7][8][9] however, there are significantly different challenges associated with managing paediatric patients in the EMS setting. [10] Evidence from the Emergency Department (ED) setting, where one in 11 children who use the service do so frequently, [11] suggests that management of paediatric patients who use services frequently can result in positive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, even intensive campaigns often fail to maintain behavioural changes since some patients will keep reaching out to the healthcare system through the emergency system. [149][150][151] This support the contradictory theories that we may miss the opportunity to assist these patient when they reach out for help, and that emergency services could be better prepared for taking care of these patients. 150,[222][223][224][225][226] In high-income countries, there is an increasing demand to reduce the number of ambulance dispatches and hospital admissions by reducing 'preventable' or 'avoidable' contacts.…”
Section: Ems Calls and Ems Responsementioning
confidence: 64%
“…[149][150][151] This support the contradictory theories that we may miss the opportunity to assist these patient when they reach out for help, and that emergency services could be better prepared for taking care of these patients. 150,[222][223][224][225][226] In high-income countries, there is an increasing demand to reduce the number of ambulance dispatches and hospital admissions by reducing 'preventable' or 'avoidable' contacts. 127,146,147 In this scenario, it can be seen as contradictory to define an overall 'lower utility of emergency services' as a stand-alone outcome measure, since there may already be an underuse or barriers to access high-quality medical care in these groups.…”
Section: Ems Calls and Ems Responsementioning
confidence: 64%
See 1 more Smart Citation